Role of non-coding RNAs and exosomal non-coding RNAs in retinoblastoma progression - Ahangar Davoodi, Nasrin; Najafi, Sajad; Naderi Ghale-Noie, Zari; Piranviseh, Ashkan; Mollazadeh, Samaneh; Ahmadi Asouri, Sahar; Asemi, Zatollah; Morshedi, Mohammadamin; Tamehri Zadeh, Seyed Saeed; Hamblin, Michael R.; Sheida, Amirhossein; Mirzaei, Hamed (Frontiers in Cell and Developmental Biology, 2022)
Retinoblastoma (RB) is a rare aggressive intraocular malignancy of childhood that has the potential to affect vision, and can even be fatal in some children. While the tumor can be controlled efficiently at early stages, metastatic tumors lead to high mortality. Non-coding RNAs (ncRNAs) are implicated in a number of physiological cellular process, including differentiation, proliferation, migration, and invasion, The deregulation of ncRNAs is correlated with several diseases, particularly cancer. ncRNAs are categorized into two main groups based on their length, i.e. short and long ncRNAs. Moreover, ncRNA deregulation has been demonstrated to play a role in the pathogenesis and development of RB. Several ncRNAs, such as miR-491-3p, miR-613,and SUSD2 have been found to act as tumor suppressor genes in RB, but other ncRNAs, such as circ-E2F3, NEAT1, and TUG1 act as tumor promoter genes. Understanding the regulatory mechanisms of ncRNAs can provide new opportunities for RB therapy. In the present review, we discuss the functional roles of the most important ncRNAs in RB, their interaction with the genes responsible for RB initiation and progression, and possible future clinical applications as diagnostic and prognostic tools or as therapeutic targets.